VIRTUAL LABORATORY AS REALISTIC TOOL FOR THE E-LEARNING IN THE ELECTRIC AND ELECTRONIC MEASUREMENT AND INSTRUMENTATION - Grimaldi, Domenico; Rapuano, Sergio; Riccio, Mariella; Zoino, Francesco (International Journal of Computing, 2014)
The paper deals with the research project adopting the e-learning methodologies for teaching in electrical and electronic measurement and instrumentation. The objective is to offer to the users the tool to achieve accurate and practical experience by working in real conditions and on real instruments. After the description of both the hardware and the software architecture of the Remote Didactic Laboratory, Laboratorio Didattico Remoto – LA.DI.RE. “G. Savastano”, the innovative solutions addressing the requirements of reality are examined and investigated. The core of the system is the Learning Management System (LMS) that provides didactic contents, enabling the account management, security protection, collaborative learning, student activity tracking, and feedback collection. LA.DI.RE. adds to the commercial LMS the innovative services dedicated to laboratory activities concerning the remote control of real instrumentation and the real-time visualization of instrument front panels during the execution of the experiment chosen by the user.